Interconnectivity of Leadership: An Analysis of the Synergistic Role of Village Leadership in Education Development - Prasetya, Subhan Muhajir; Aufa, Rinjani (Development: Studies in Educational Management and Leadership, 2025)
This study examines the relationship between leadership functions and employee performance, with a particular focus on efforts to mitigate employee arrogance. Using qualitative methods with purposive sampling techniques, primary data was obtained through interviews, observations, and documentation, supplemented by secondary data. The researcher acted as the primary instrument with interview guides and field notes. Data analysis followed the Miles & Huberman model: data reduction, presentation, and conclusion drawing. The results show that effective leadership functions—including instructive, consultative, participatory, delegative, and controlling—play a crucial role in reducing employee arrogance. This study also highlights the importance of assertive leadership in decision-making so that employees consistently carry out their core tasks and functions, as well as the need for regular and structured socialization. On the other hand, work motivation, education level, and work experience also contribute to reducing arrogance, while limited facilities and inadequate infrastructure are inhibiting factors. Overall, these factors have a significant impact on employee attitudes, discipline, and performance as a whole.